Role And Place of Statistical Acceptance Control of Products - Ergashov Qahramon Mixoilovich (Zien Journals, 2022)
In production lines, product quality is determined by the acceptance method, in which a defective product can pass the sampling test stage. That is why product quality control can be carried out by a continuous method. This method uses a sampling of individual items from which it is possible to determine which type of product can be defective
Keywords: Product quality; selective control; continuous control; probability theory and mathematical